THE RELATIONSHIP NURSE KNOWLEDGE ABOUT PREVENTION NOSOCOMIAL INFECTIONS IN TANJUNG ROOM RSUD DR. RM DJOELHAM BINJAI 2020 - Sapnita Sapnita (Institute of Computer Science (IOCS), 2020)
Nosocomial infections, also known as hospital-acquired infections, occur in patients hospitalized for at least 72 hours. These patients do not show symptoms of infection when they enter the hospital. The type of research used was a chi-square test with a cross-sectional study design. The purpose of the study was to determine the relationship between nurses' knowledge about the prevention of nosocomial infections at Dr. Rm Djoelham Binjai Hospital. The population in this study amounted to 30 nurses who worked at Dr. Rm Djoelham Binjai Hospital, with a sample of 30 nurses. ) = 0.05 and df = 1 obtained from the calculation results, namely Asymp. Sig. (2-sided) 0.001 < p-value 0.05, Ho is rejected, and Ha is accepted. The relationship between nurses' knowledge about preventing nosocomial infections at Dr. Rm Djoelham Binjai Hospital. It is recommended that nurses continue to increase their knowledge of preventing nosocomial infections from avoiding an increase in the number of nosocomial infections.